Hybrid management of a large atrial septal defect and a patent ductus arteriosus in an infant with chronic lung disease - Pedra Simone; Jatene Marcelo; Pedra Carlos (Wolters Kluwer Medknow Publications, 2010)
We report a case wherein a dysmorphic four-month-old infant (weighing 4.5 kgs) with an 8 mm atrial septal defect (ASD), a 1.5 mm patent ductus arteriosus (PDA), a 2 mm mid-muscular ventricular septal defect (VSD) associated with chronic lung disease, and severe pulmonary hypertension, was successfully managed using a hybrid approach, without the use of cardiopulmonary bypass (CPB). Through a median sternotomy, the PDA was ligated and the ASD was closed with a 9 mm Amplatzer septal occluder implanted through peratrial access. The VSD was left untouched. Serial echocardiograms showed complete closure of the ASD and PDA, with progressive normalization of the pulmonary artery (PA) pressures within three months. The child rapidly gained weight and was weaned from sildenafil and oxygen administration. After 12 months, the VSD closed spontaneously and the child remained well, with normal PA pressures. A hybrid approach without the use of CPB should be considered in the management of infants with congenital heart disease, associated with chronic lung disease and pulmonary hypertension.